2019
DOI: 10.1016/j.ecolecon.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Did transition bring cleaner air? Effects of ownership, territorial and technology policy on air pollution

Abstract: The paper investigates trends in air pollution in Poland during transition to a market economy. By analysing how the EU, national and regional development policy mix affects environmental outcomes we show the importance of context in terms of assessing the contribution to air pollution of different stakeholders such as foreign investors. The results show that while state owned firms pollute more, new domestic firms make a positive contribution to reducing emitted particulate matter and foreign owned subsidiari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…This is also, in part, because foreign firms are found to transfer, on average, cleaner technologies to China relative to what the private sector has adopted in this country. Very similar results were also found in Jensen and Mina (2019) in the context of Poland. Here similar pre-conditions exist in terms of inherited firms and technologies owing to the previous economic system.…”
Section: Literature Reviewsupporting
confidence: 86%
See 1 more Smart Citation
“…This is also, in part, because foreign firms are found to transfer, on average, cleaner technologies to China relative to what the private sector has adopted in this country. Very similar results were also found in Jensen and Mina (2019) in the context of Poland. Here similar pre-conditions exist in terms of inherited firms and technologies owing to the previous economic system.…”
Section: Literature Reviewsupporting
confidence: 86%
“…In particular, the last issue critically requires stronger and more valid evidence, and only 4–7 studies were found in the literature that could be argued to have come close towards overcoming this major hurdle of investigation (with firm-level indicators - Eskeland and Harrison, 2003 , Javorcik and Wei, 2003 , Jiang et al., 2014 , Huang and Chang, 2019 and with territorial aggregates Greaney et al. (2017) , Shi and Xu (2018) and Jensen and Mina (2019) ). For example, out of the 13 firm-level studies on the impacts of inward or outward foreign direct investment (FDI) location decisions related to green behaviour reviewed by Dechezleprêtre and Sato (2017) , only one of the reported studies ( Eskeland and Harrison, 2003 ) included measures that directly equate with negative externalities such as energy intensity, pollution cost, or emissions of pollutants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the process of this adjustment, there are apparent differences in the production efficiency, pollution emission intensity, and pollution control strategies of these industries (Gross and Solymossy, 2016;Zhang et al, 2022). The transition from traditional inefficient industries to capitaland technology-intensive industries can not only improve the use of resources, but also contribute to the preservation of the ecological environment (Crotty, 2002;Jensen and Mina, 2019). From the provincial level, the industry changes in the jurisdiction can be manifested as the increase of green TFP in total.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Such as green growth policies could result in a virtuous shift towards high value-added sectors [ 21 ]. The local governance (e.g., renewable technologies or services) had been proved very effective in reducing emissions of particulate matter [ 22 ]. Normally, economic growth is thought to be an acceptable way of strengthen the social and environment sustainability for all nations [ 23 ].…”
Section: Literature Reviewmentioning
confidence: 99%